2019
DOI: 10.1002/smtd.201900196
|View full text |Cite
|
Sign up to set email alerts
|

Pure Bromide‐Based Perovskite Nanoplatelets for Blue Light‐Emitting Diodes

Abstract: Metal halide perovskites witness a huge development in light‐emitting diodes (LEDs) triggered by their unique optical and optoelectronic properties. However, blue emission perovskite LEDs lag behind their red and green counterparts in efficiency, due to the difficulties in synthesizing stable materials and maintaining quantum efficiency in thin films as high as in solution. The nanoplatelets (NPLs), with exciton binding energies up to several hundreds of meV, exhibit fundamentally different excitonic behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 119 publications
0
39
0
Order By: Relevance
“…Substantial efforts have been made in the past several years to obtain blue perovskite emitters, such as perovskite nanocrystals (NCs), [ 19–25 ] 2D perovskite nanoplatelets, [ 26–32 ] and quasi‐2D perovskites. [ 33–39 ] In particular, the quasi‐2D perovskites are rising as efficient luminescent materials for highly performed blue PeLEDs due to the cascade energy landscape for efficient exciton transfer and the subsequent radiative recombination.…”
Section: Figurementioning
confidence: 99%
“…Substantial efforts have been made in the past several years to obtain blue perovskite emitters, such as perovskite nanocrystals (NCs), [ 19–25 ] 2D perovskite nanoplatelets, [ 26–32 ] and quasi‐2D perovskites. [ 33–39 ] In particular, the quasi‐2D perovskites are rising as efficient luminescent materials for highly performed blue PeLEDs due to the cascade energy landscape for efficient exciton transfer and the subsequent radiative recombination.…”
Section: Figurementioning
confidence: 99%
“…[ 5,6 ] However, the PLQY of blue‐emitting perovskite has struggled to match this such admirable value. [ 7–11 ] This exceedingly unbalanced development of three primary colors triggered by the low blue photoluminescence efficiency seriously hinders the further practical application of perovskite. [ 12–14 ] Although recent remarkable efforts have been devoted to remedy this regret, [ 15–18 ] at present, it is generally recognized that achieving high blue emitting PLQY with stable and pure spectra is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In general, two strategies have been developed to achieve blue emission: Dimension engineering and component engineering. [ 8,13,20–22 ] The dimension engineering is constructing quantum well structures by synthesizing 2D or quasi‐2D Br‐based perovskite, allowing the emission wavelength to shift toward the blue region based on the quantum confinement effect. [ 23 ] Recently, lots of outstanding work regarding dimension engineering have greatly promoted the research of blue emitting perovskite.…”
Section: Introductionmentioning
confidence: 99%
“…[28] The efficiency gap has been reduced in the past two years; quite recently, a record EQE of 12.3% was demonstrated for blue PeLEDs based on high-quality CsPbBr3 perovskite QDs. [32] [113] The low PLQY of blue perovskites is an impediment to high-performance blue PeLEDs. [114] Previous studies have revealed that the PLQY dramatically decreases as the light emission shifts to the blue region.…”
Section: Developments and Statusmentioning
confidence: 99%